2014
DOI: 10.1515/nbec-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation Phenolic Compounds in Cell Culture of Vitis vinifera L. by Phaeomoniella chlamydospora

Abstract: The in vitro cell cultures of Vitis vinifera L. cv. St. Laurent were treated with two elicitors - synthetic methyl jasmonate and natural, prepared from grapevine plant infected with the Phaeomoniella chlamydospora, the agent causing the Esca disease of grapevine. Efficiency of phenolic compounds production after elicitation of cell culture was analysed immediately after treatment (15 min, 30 min, 60 min) and later (after 24, 48, and 72 hours). The cell growth and content of phenolic compounds (+)-catechin, (-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
(26 reference statements)
1
6
2
Order By: Relevance
“…B). Similar increases in syringaldehyde and vanillin contents were comparable to previous studies in Phaeomoniella‐ infected grapes (Sák et al ) and Verticillium ‐infected tomatoes (Gayoso et al ), respectively. Accumulation of syringaldehyde in oil palm plantlets during infection matched the results obtained from Maúle reagent, which is a result of the induction of sinapyl alcohol specific isoforms of CAD during the biosynthesis of lignin (Mitchell et al ).…”
Section: Resultssupporting
confidence: 90%
“…B). Similar increases in syringaldehyde and vanillin contents were comparable to previous studies in Phaeomoniella‐ infected grapes (Sák et al ) and Verticillium ‐infected tomatoes (Gayoso et al ), respectively. Accumulation of syringaldehyde in oil palm plantlets during infection matched the results obtained from Maúle reagent, which is a result of the induction of sinapyl alcohol specific isoforms of CAD during the biosynthesis of lignin (Mitchell et al ).…”
Section: Resultssupporting
confidence: 90%
“…It may be concluded that the polyphenolic content was highest on BAP enriched media with the lowest value being recorded from media enriched with NAA. The maximum polyphenolic content for this study (1.42 mg/g FW) is much lower than that reported by Sák et al, 2014 [20], with a grapevine callus (cv. St. Laurent) which amounted to 2.86 mg/g FW in the basal medium cultures.…”
Section: Resultscontrasting
confidence: 72%
“…It is important to state that the callus was grown in conditions with 16/8 h day/night photoperiod. It should also be stressed that this callus was not treated with any elicitors, so treatment with any elicitor such as methyl jasmonate from Phaeomoniella chlamydospora [20,21], or UV [22,23,24] or anything which might stress the vine might very well give very different results. This shows that in vitro anthocyanins could be produced all year round [25].…”
Section: Resultsmentioning
confidence: 99%
“…Plant cells cultivated in vitro such as callus or cells suspension culture could potentially be competitive systems for effective production of marketable secondary metabolites possessing biological activities [10]. Moreover, the production of bioactive secondary metabolites can be enhanced by the treatment of the undifferentiated cells with elicitors [11].…”
Section: Introductionmentioning
confidence: 99%